Orthognatic Surgery And Treatment: An Islamic Legal Maxims Analysis - Ahmad Tarmidzi, Nor Azura; Wan Ismail, Wan Abdul Fattah; Nik Salleh, Nik Salida Suhaila; Mochammad Sahid, Mualimin; Ramli, Haslinda; Mohamed Ramli, Nalisha; Halib, Nadia; Abdul Ghaffar, Nur Akilah (IIUM Medical Journal Malaysia, 2017)
Introduction: The position of facial bones contribute great impact to the shape of the face. Shape of these underlying facial bones responsible for a person facial proportions, angles and contours. Facial deformity can either be congenital or acquired. Functional impairment related to facial deformity include chewing problems, breathing problems, speech impairments and temporomandibular joint pathology. Orthognathic surgery is a procedure involving incision and manipulation using instrument to align the jaws. Performing cosmetic surgery seems to change the creation of Allah and the original law of changing Allah creation is prohibited. Materials and Methods: The approach use in this study is based on analysis of Quran, Sunnah, views of ulama and contemporary fatwas. Results: In assessing the orthognathic surgery law for patients with this dentofacial defect, the researcher found that the main issues that need to be investigated are the difficulties existed (Masyaqqah) and the level of patient harm in addition to the intention or purpose of performing orthognathic surgery. However, according to the principles of the Islamic jurisprudence, orthognathic surgery is permitted based on the principles such as ad-darar yuzal, almusyaqqah tajlibu al-taisir, al-darurat tuqaddiru biqadaruha, Irtikab Akhaf Al-Dhararain and aldarurat tubihu mahzurat serta al-Umur bimaqasidiha. Conclusion(s): Orthognathic surgery is permissable because the purpose is not to alter the original look but as measurement to treat defects and to restore function. This objective is very consistent with the fiqh rules that stated, every harm and distress should be eliminated.